Current Limitations of Murine Models in Oncology for Ascorbate Research - Campbell, Elizabeth J.; Dachs, Gabi U. (Frontiers in Oncology, 2014)
The role of vitamin C (ascorbate) in cancer prevention, tumour growth and treatment is of intense public interest. Clinical trial data has been sparse, contradictory and highly controversial, and robust preclinical data is required for progress. This paper reviews preclinical models and their limitations with respect to ascorbate research. Most studies have utilised animals able to synthesise ascorbate and thus are not ideal models of the human condition. More recently, genetically modified mouse models have become available, yet all studies compared healthy and scorbutic mice. The majority of investigations to date concluded that increased ascorbate led to decreased tumour growth, but data on mechanisms and doses are inconclusive. Clinically relevant animal studies are still required to convince a generally sceptical medical audience of the potential worth of ascorbate as an adjunct to therapy.